Simulation of vertical characteristics and in-wheel motor vibration of electric vehicles with asymmetric suspension damper under road impact. (2nd January 2019) - Zhao, Leilei; Yu, Yuewei; Zhou, Changcheng; Mao, Shaofang; Yang, Fuxing
Abstract: For wheel-drive electric vehicles (WDEVs), it has become an urgent problem how to eliminate the adverse effects of the in-wheel motor on ride comfort and to reduce the road impact on the motor. The aim of this paper is to explore the effect rule of the suspension damper damping on the vertical characteristics and the motor vibration of WDEVs under road impact, so as to provide theoretical guidance for the design of WDEVs. Firstly, by considering the nonlinear damping characteristics of the damper, the nonlinear dynamic model of WDEVs is established. Secondly, according to the national standard GB/T 4970-2009, the triangular bump model is created and the evaluation indexes are introduced for WDEVs under road impact. Thirdly, through a case study, the evaluation indexes of a WDEV with different damper damping characteristics are numerically simulated and analyzed. Finally, the evaluation indexes are normalized and the comprehensive performance evaluation is carried out using a radar chart. The results show that under the triangular bump impact, the WDEV with the damper rebound damping less than the compression damping behaves better in terms of comprehensive performance, which is more favorable to avoid the motor damage.